Low-dose heparin for prolonging the patency of peripheral intravenous catheters in adults a systematic review and meta-analysis - Kumar, Manoj; Vandermeer, Ben; Bassler, Dirk; Mansoor, Nadia (International Journal of Medicine, 2014)
Objective:Â To assess evidence from randomized controlled trials (RCTs) about the efficacy of low-dose heparin for prolonging patency of peripheral intravenous catheters in adults.Design:Â Systematic review and meta-analysis.Data Sources: We searched MEDLINE, EMBASE, CINAHL and Cochrane Central Register of Controlled Trials (CCTR) to identify studies up to July 6, 2012. Additional citations were retrieved from the bibliography of the selected articles. No language restrictions were placed.Eligibility criteria for selecting studies: The eligible studies were RCTs of low-dose heparin, used as continuous infusion or as intermittent flush, through peripheral intravenous catheter as compared to a control; and measured any one of the following outcomes: duration of catheter patency, occlusion rates or local site reactions such as thrombophlebitis.Results:Â Eight RCTs were identified (5 testing heparin as continuous infusion and 3 as intermittent flush). Catheters using heparin infusions had longer patency [Mean difference = 13.37 hours, 95%CI (3.37, 23.37), p=0.009], however, no difference in the duration of patency was noted from its use as intermittent flushing solution. Similarly, continuous infusion of heparin resulted in approximately 50% lower rates of infusion failures [rate ratio = 0.50, 95%CI (0.33, 0.76), p=0.001] and phlebitis [rate ratio = 0.47, 95%CI (0.31, 0.73), p<0.001] compared to no difference noted with its use as intermittent flushing solution. Few studies reported treatment related adverse events.Conclusion:Â Low-dose heparin used as continuous infusion in PIV catheters resulted in longer catheter patency with lesser episodes of infusion failures and phlebitis. Heparins use as intermittent flush solutions had no benefit.Â Keywords: Heparin, Patency, Infusion Failure, Phlebitis, Systematic Review